2010
DOI: 10.1016/j.jjcc.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Difference in risk factors between acute coronary syndrome and stable angina pectoris in the Japanese: Smoking as a crucial risk factor of acute coronary syndrome

Abstract: The risk factors were significantly different between initially diagnosed ACS and SAP. Smoking was a more important risk factor of initially diagnosed ACS. Smoking cessation might have a preventive effect on subsequent cardiac events. Also, we found that treatment with a calcium-channel blocker would help prevent ACS in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
1
30
0
1
Order By: Relevance
“…All patients were classified as non-smokers, quitters, or persistent smokers. Smokers were defined as patients who had smoked cigarette for at least 1 year and still smoked or at least smoking within 1 month before baseline interview [9]. Non-smokers defined as patients who had never smoked cigarettes regularly [10].…”
Section: Methodsmentioning
confidence: 99%
“…All patients were classified as non-smokers, quitters, or persistent smokers. Smokers were defined as patients who had smoked cigarette for at least 1 year and still smoked or at least smoking within 1 month before baseline interview [9]. Non-smokers defined as patients who had never smoked cigarettes regularly [10].…”
Section: Methodsmentioning
confidence: 99%
“…The mean age of the patients in the study was 58.63 which was in fact almost in line with other studies. 13 Montalescot et al stated that prevalence of angina in population-based studies increases with age in both sexes, from 5-7% in women aged 45-64 years to 10-12% in women aged 65-84 and from 4-7% in men aged 45-64 years to 12-14% in men aged 65-84. 14 Interestingly, angina is more prevalent in middle-aged women than in men, probably due to the higher prevalence of functional CAD such as microvascular angina in women 15 , whereas the opposite was true in the elderly.…”
Section: Age Distributionmentioning
confidence: 99%
“…Yagi H et al 13 found that MA is also common in nondiabetic, nonhypertensive population and is an independent indicator of cardiovascular morbidity.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…The prevalence of coronary artery disease largely depends on lifestyle among which smoking, diet and exercise can be mentioned (2,3). Cardiovascular disease is the most important cause of morbidity and mortality in the world (4).…”
Section: Introductionmentioning
confidence: 99%